2010
DOI: 10.1007/s12237-010-9279-0
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Macrophyte Distribution and Abundance in Estuarine Mangrove Lakes and Estuaries: Relationships to Environmental Variables

Abstract: Annual mean salinity, light availability, and sediment depth to bedrock structured the submerged aquatic vegetation (SAV) communities in subtropical mangrove-lined estuaries. Three distinct SAV communities (i.e., Chara group, Halodule group, and Low SAV coverage group) were identified along the Everglades-Florida Bay ecotone and related to water quality using a discriminant function model that predicted the type of plant community at a given site from salinity, light availability, and sediment depth to bedrock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Overall, SAV biomass and species number were consistently higher in the fresh and intermediate assemblages throughout the year. Fresh and intermediate assemblages were composed of up to 10 species, while brackish and saline assemblages were restricted to 2 consistently present species, similar to findings reported across other regions reporting up to 3 species in the higher salinity zones (Orth & Moore 1988, Dunton 1990, Frankovich et al 2011. For example, only 2 species, Ruppia maritima and Zostera marina are found in the saline areas of Chesapeake Bay (Patrick & Weller 2015), and only 3 species (Halodule wrightii, Thalassia testudinum, Syringodium filiforme) dominate many saline lagoons in Texas, with only 1 species, R. maritima, reported in some saline Mexican lagoons (Flores-Verdugo et al 1988, Dunton 1996.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, SAV biomass and species number were consistently higher in the fresh and intermediate assemblages throughout the year. Fresh and intermediate assemblages were composed of up to 10 species, while brackish and saline assemblages were restricted to 2 consistently present species, similar to findings reported across other regions reporting up to 3 species in the higher salinity zones (Orth & Moore 1988, Dunton 1990, Frankovich et al 2011. For example, only 2 species, Ruppia maritima and Zostera marina are found in the saline areas of Chesapeake Bay (Patrick & Weller 2015), and only 3 species (Halodule wrightii, Thalassia testudinum, Syringodium filiforme) dominate many saline lagoons in Texas, with only 1 species, R. maritima, reported in some saline Mexican lagoons (Flores-Verdugo et al 1988, Dunton 1996.…”
Section: Discussionsupporting
confidence: 84%
“…These gradients vary across and between estuaries, and inter-and intra-annually in response to landscape variation, climatic cycles, disturbance and management. Along estuarine environmental gradients, SAV distribution and biomass vary spatially and temporally, responding rapidly to changing water salinity, light and nutrient conditions resulting from precipitation, storm events and human activities (Frankovich et al 2011, Correia et al 2012, DeMarco et al 2018, Patrick et al 2018. The resulting temporal and spatial variation in the environment determine the composition of SAV assemblages through direct and indirect impacts on species survival, reproduction and growth rates, ultimately defining the distribution, abundance and composition of the community (Fourqurean et al 2001, Patrick et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…We found that higher sediment phosphorus in the western ecotone predicted an increase in total and germinated R. maritima seeds based on regression analysis. The higher sediment nutrients in the western ecotone likely provide R. maritima with reproductive opportunity to quickly develop sexually reproductive shoots with a high biomass and produce seeds when other conditions (light, hydrology and salinity) are conducive for germination and growth (e.g., Frankovich et al, 2010;Strazisar et al, 2013). Our finding that seed coat fragments increased as a function of sediment P suggests that sediment nutrients are important not only for seed production in the western ecotone, but also for embryo development during the recruitment process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the low salinity appears to facilitate the dominance of Halodule over Thalassia, and the increase in nutrients appears to facilitate the high abundance of puff taxa that utilize Halodule leaves as attachment substratum. If nutrient levels keep increasing nearshore, a shift from a Halodule-Chara-dominated system towards an alternative one dominated by microalgae and phytoplankton can be expected (Frankovich et al 2011).…”
Section: Discussionmentioning
confidence: 99%